GEOCHRONOLOGICAL ASPECT OF THE GEOCHEMISTRY OF STABLE ISOTOPES IN GEOTHERMAL WATERS - Ustinov V.I.; Grinenko V.A.; Taran Yu.A.; Barsukov L.A. (My University, 1989)
The theoretical possibility of using stable isotopes for geochronological purposes, based on the kinetics of isotope exchange reactions, was demonstrated in a study of the distributions of the isotopes of light elements in water and sediments of the Red Sea. In the present paper we discuss procedural approaches to the use of stable isotopes for dating purposes and describe techniques for determining certain parameters of the hydrothermal system, i.e., the residence time of water in the heated zone and the rate at which solutions migrate to the surface. Availability of such information on the properties of geothermal reservoirs will improve the effectiveness of prospecting for thermal waters, and this fact also emphasizes the importance of such investigations in isotope geochemistry.